Impact of Performance Appraisal on Education Quality with Employee Engagement as Intervening Variable in Islamic Schools in Sukabumi City - Berliana, Berliana; Syahlan, Fatra; Edy Rachmadio, R.; Amir, Miftah; Joko, Joko; Nugraha, Derry (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
This study examines the relationship between performance assessment practices and educational quality in educational institutions, with specific focus on employee engagement as an intervening variable. While extensive research has explored human resource management practices in educational settings, limited attention has been given to the mediating mechanisms through which performance assessment influences educational outcomes. Using Structural Equation Modeling (SEM) with AMOS, this research tested a theoretical model positing that performance assessment affects educational quality both directly and indirectly through enhanced employee engagement. Data were collected from 347 educational staff (67.7% teaching staff, 23.6% administrative staff) across various educational institutions using validated survey instruments. Results confirmed that performance assessment significantly influences educational quality directly (β = 0.32, p < 0.001) and indirectly through employee engagement (β = 0.26, 95% CI [0.18, 0.35], p < 0.001), supporting partial mediation. The dimensions of performance assessment that most strongly contributed to this relationship were assessment criteria clarity and feedback quality. Multi-group analysis revealed that the mediating effect was stronger for teaching staff compared to administrative staff. These findings contribute to the integration of human resource management and educational leadership theories by demonstrating how performance assessment practices influence educational outcomes through both direct instrumental effects and indirect motivational pathways. For educational leaders, the study highlights the importance of designing comprehensive performance assessment systems that not only provide clear standards and constructive feedback but also foster engagement by emphasizing fairness, development orientation, and staff participation. Future research should employ longitudinal designs to establish causality more definitively and explore additional mediating variables to develop a more comprehensive model.